Local Control by Mastectomy in Advanced Breast Cancer with Liver Metastasis after Chemotherapy, Radiotherapy, and Hyperthermia - A Case Report - Ishizuka, Mariko; Tsubota, Yu; Ueda, Aiko; Sueoka, Noriko; Yoshikawa, Katsuhiro; Yamamoto, Daigo (Gan to kagaku ryoho, 2018)
Advanced breast cancer has a poor prognosis compared to early breast cancer; however, quality of life and radical operation can be improved in some case by using multidisciplinary treatment. A 54-year-old woman was examined at the hospital because of an enlarging tumor in the left breast. She was aware of a lump for 3 years. Results of the initial examination indicated invasive ductal carcinoma with liver metastasis. She first received chemotherapy(AC followed by weekly paclitaxel). After 4 courses of weekly paclitaxel, computed tomography revealed axillary lymph nodes involved in the axillary vein. Operation was difficult and conversion therapy was administered. The patient underwent radiotherapy, hyperthermia, and hormone therapy. After 1 year from the start of hormone therapy, the metastasis had disappeared and the patient underwent operation in our unit. Eight months after operation, no recurrence was observed.